ISLA a renewable energy-diesel hybrid system design framework for island communities in the Philippines (an application in Banton Island, Romblon) - Corpuz, Jayson G.; Tamayao, Mili-Ann M. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
This study developed an RE-diesel hybrid system design framework for off-grid island communities in the Philippines, called ISLA. This framework is meant to guide investors and developers in making decisions that will efficiently and economically utilize renewable energy resources alongside the currently used diesel-based power plants. Renewable energy (RE) investors and developers in off-grid island areas face the challenge of improving availability and reliability of power supply while reducing the overall cost of power generation and mitigating environmental impact. Many off-grid island communities with access to electricity are powered by small diesel-based power plants. Maintaining and operating small diesel-based power plants, however, entail substantial resources due to the high fuel, transportation and handling costs that translates to higher electricity price. The combustion of diesel also increases criteria air pollutants and greenhouse gas emissions. Integrating renewable energy (RE) technologies to these diesel-based power plants is seen as a potential solution towards providing more sustainable energy systems to off-grid island communities. However, designing and developing such a system involves rigorous techo-economic analysis. ISLA is meant to provide a systematic approach on how to asses and develop RE-diesel hybrid applications. ISLA is foreseen to guide interested RE developers and energy sector stakeholders, especially the Electric Cooperatives (ECs), through the planning process of technically sound and commercially viable diesel-RE hybrid schemes. The framework includes meteorological data generation, selection of simulation tool or software for optimization, standards and limits for choosing the appropriate components for the systems, incorporation of cost of externalities like penalty of emissions produced, development of financial model using local values, and market options for development. ISLA also provides and identifies sources for the data that are needed in implementing the method. The framework can help to guarantee the lowest investment with full use of renewable energy resources and battery bank, so that the hybrid system exhibit the best conditions in terms of investment and system reliability. This also includes economical objectives and requires the assessment of the system's long term performance in order to reach the best compromise for both reliability and cost. The framework was employed in designing a diesel-RE hybrid system in Banton Island, Romblon. Results show significant decrease on the electricity tariff, government subsidy, emissions produced, fuel consumption and imported oil dependence while providing 24-hour service to the people. The framework can be further improved by incorporating an annual load growth in the simulation that is informed by current data from field surveys that determine the energy consumption profile of the island. Ease of use may also be improved by developing a software with an intuitive user-interface. Studies that model the response of communities to increased energy supply may also be helpful in providing more accurate information that can help in developing better systems for the long-term.
Thesis (M.S. Energy Engineering)--University of the Philippines Diliman
Keywords: Renewable energy; Renewable natural resources -- Philippines -- Romblon (Province)